Discussion, demonstration and motivation influence to achievement learning of accounting study field - Yoyok Soesatyo, Priyono, Sunda Ariana (Opción, 2019)
This study aims to determine differences in learning outcomes and interactions, between demonstration and discussion learning, and who have high learning motivation and low learning motivation. Two-way variance data analysis technique is used by applying questionnaires and test methods of data collection techniques. The results of the calculations, which were conducted by using two-way variance, showed that there were influences and differences in learning outcomes for students taught through demonstrations, and discussion lessons were conducted in accounting lessons.